2017
DOI: 10.1108/gm-01-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Relating multidimensional perfectionism and academic procrastination among Indian university students

Abstract: Purpose This study aims to examine the impact of multidimensional perfectionism on academic procrastination among university students in India and to explore whether gender plays any role in this relationship. Design/methodology/approach Data were collected from a sample of 90 female and 60 male students, aged 18-23 years, enrolled in full-time bachelor’s and master’s programs in a central university in the National Capital Region of India and analyzed adopting different statistical techniques. Findings Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 103 publications
1
18
0
2
Order By: Relevance
“…The results indicated that academic procrastination positively correlates with all the dimensions of perfectionism. Gender differences exist with regard to other-oriented perfectionism, socially prescribed perfectionism and academic procrastination (38).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that academic procrastination positively correlates with all the dimensions of perfectionism. Gender differences exist with regard to other-oriented perfectionism, socially prescribed perfectionism and academic procrastination (38).…”
Section: Previous Studiesmentioning
confidence: 99%
“…One study revealed that self-oriented perfectionism and academic procrastination were positively associated (9). However, many studies ascertained a negative association between the self-oriented perfectionism and procrastination (33), (37), and (38).…”
Section: Research Question 2 What Is the Relationship Between Perfecmentioning
confidence: 99%
“…On the other hand, negative and positive perfectionisms were found to be negative and positive predictors for academic achievement, respectively in an Iranian study (Roohafzaet al, 2010). Besides having an influence in academic achievement, it has also been demonstrated that academic procrastination was moderately and significantly correlated to SOP and OOP (p<0.01), and strongly correlated to SPP (p<0.01) (Ghosh and Roy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the published literature, researchers have differing opinions on gender differences in perfectionism. While some have shown that gender does not play a role in perfectionism , others have demonstrated gender differences in perfectionism (Ghosh & Roy, 2017;Landa & Bybee, 2007). Other demographic factors that have been shown to have an influence on perfectionism include socioeconomic status (Krstic & Kevereski, 2015;Lyman & Luthar, 2014), and ethnicity (Chang, 1998).…”
Section: Demographic Factors and Perfectionismmentioning
confidence: 99%
“…Por otra parte, la procrastinación académica es influida por: a) la necesidad de cognición , definida ésta como la motivación y preferencia que muestran las personas hacia la actividad de pensar (Cacioppo & Petty, 1982), b) el perfeccionismo (Closson & Boutilier, 2017;Ghosh & Roy, 2017), c) las configuraciones del Síndrome de Atención Cognitiva , la depresión y las metacogniciones (Fernie, Bharucha, Nikčević, Marino & Spada, 2017); este síndrome, en lo particular, se constituye por un conjunto de patrones desadaptativos configurados por creencias metacognitvas específicas y planes que controlan el uso del pensamiento y la atención (Wells, 2000), y En el caso de las investigaciones realizadas en idioma español el escenario está dominado especialmente por los investigadores peruanos (Alegre, 2013;Domínguez-Lara, 2017a;Domínguez-Lara, 2017b;Domínguez-Lara & Campos-Uscanga,2017;Domínguez, Villegas & Centeno, 2014;Matalinares, et al 2017;Olazábal & Zegarra, 2017;Paz, Aranda, Navarro, Delgado & Sayas, 2014;Rodríguez, 2017;y Yarlequé, et al 2016); siendo esta presencia también evidente en las tesis de las universidades peruanas como sería el caso de la Pontificia Universidad Católica del Perú (Vallejos, 2015), la Universidad Peruana Unión (Rafael & Ramírez, 2016) Ante esta situación, se considera necesario realizar la validación psicométrica de esta escala si se desea seguir investigando al respecto y contar con la seguridad de estar haciendo una buena medición de esta variable. Esta necesidad, predominantemente de carácter teórico-conceptual e instrumental, tiene implicaciones prácticas para los procesos educativos al ser un fenómeno que afecta a los estudiantes de educación media superior y superior.…”
Section: Introductionunclassified